Analisis Desain Pembelajaran SD Kelas Rendah - Kurnia Fartdillah; Resti Hidayat; Dar Alifah .A (FONDATIA, 2020)
In managing a learning, here the role of teachers is to understand how teachers manage the class, especially managing low classes that are essentially the characteristics of students are still in the early stages of development, so here teachers Must be able to master how to manage the class so that learners in the early stages of the low class are capable of mastering a material and understanding the material being taught. This research is a descriptive study conducted in class III students (3) Si SDN SANGIANG 03 Tanah Merah, Sepatan Tangerang. Here we do a research that analyzes how the design of learning is happening in low-grade students or early-stage students. Data from observations and interviews will be processed by explaining how and analyzing the data until it finds conclusions. From the results of the research detected that SDN SANGIANG 03 in the design of the study prioritizes the media talks in the teaching process can also use other media such as pictures, concrete objects according to the material to be studied so that Such media should be used in explaining the material. In this school also does not use group learning models because the number of students in every class is inadequate so it is difficult for teachers to apply group learning to students because it is influenced also by the lack of classes in this school.